Consumers Avoid Buying From Firms With Higher CEO‐to‐Worker Pay Ratios - Mohan, Bhavya; Schlager, Tobias; Deshpandé, Rohit; Norton, Michael I. (Journal of Consumer Psychology, 2018)
We document a novel driver of consumer behavior: pay ratio disclosure. Swiss corporation performance data gathered during a legally mandated pay ratio referendum reveals that salient high pay ratios are associated with decreased firm sales (Pilot Study). An incentive‐compatible field experiment shows that, when ratios are revealed, consumers avoid firms with high ratios relative to competitors (Study 1). Finally, the effect of high pay ratios also depends on consumers’ political ideology: Democrats and Independents show decreased purchase intentions for products sold by firms with high ratios, whereas Republicans are unaffected (Study 2).